Notes on the genus Neope Moore, [1866] from India (Lepidoptera: Nymphalidae, Satyrinae) - Das, G. N.; Singh, N.; Chandra, K. (SHILAP Revista de lepidopterología, 2021)
The genus Neope Moore, [1866], currently consisting of six species and two additional subspecies from India, is reviewed based on a study of recent materials. A detailed taxonomic treatment of the genus Neope from India has been provided along with description of genitalia structures, a gap area for the Indian fauna of Neope. The male genitalia as well as external characters of Neope armandii khasiana Moore, 1881 is described from India for the first time.